Serological Methods for Detection and Identification of Viral and Bacterial Plant Pathogens-A Laboratory Manual. - and S. H. DeBoer, Editors, R. O. Hampton, E. M. Ball (Indian Phytopathology, 2002)
Another excellent publications by the American Phyto-pathological Society. The manual covers over fifty topics contributed by well known experts in the application ofserological methods for detection and identification of viral and bacterial plant pathogens. Methods have been given for the isolation and purification of viral (M. Brakke) and bacterial (S. DeBoer and N. Schaad) antigens, production of polyclonal (E.Ball et al.) and rrionoclonal (R. Jordan and S. DeBoer) antibodies, globulin conjugation (D. Mackenzie) and amplification systems (D. Durand).